The Influence of Hedonic Value and Economic Value on Continuance Intention with Satisfaction as an Intervening Variable - Lianto, Fazrian; Dewi, Citra Kusuma; Widodo, Arry; Rubiyanti, Nurafni; Silvianita, Anita (East Asian Journal of Multidisciplinary Research, 2024)
People's behavior towards transportation services has formed new habits in using services for ordering goods and services, especially in terms of ordering ride-hailing services via online-based applications. Gojek, which is one of the most popular ride-hailing applications in Indonesia, is ranked second as the most widely used ride-hailing application in Indonesia. This research aims to determine the influence of Hedonic value and Economic value on the Continuance intention of the ride-hailing application (Gojek), with Satisfaction as an intervening variable. The population in this study are users of ride-hailing services from Gojek in Indonesia, as well as a sample consisting of individuals who meet the criteria for being users of the Gojek application. This research method uses a quantitative approach by applying Smart-PLS analysis.